Pancreaticoduodenectomy for Retroperitoneal Sarcomas: A Mono-Institutional Experience in China - Li, Cheng-Peng; Wang, Zhen; Liu, Bo-Nan; Lv, Ang; Liu, Dao-Ning; Wu, Jian-Hui; Qiu, Hui; Hao, Chun-Yi (Frontiers in Oncology, 2020)
Background: En bloc resection of retroperitoneal sarcoma (RPS) with adjacent organs such as pancreatic head and duodenum is challenging for surgeons. This mono-institutional study is aim to evaluate the feasibility, safety, and outcome of performing pancreaticoduodenectomy(PD) during RPS resection. Methods: The clinical data of RPS patients who underwent PD at the Sarcoma Center of Peking University Cancer Hospital from January 2011 to December 2019 was collected and analyzed. Results: Twenty-seven patients out of a total of 264 surgically treated RPS underwent PD. The main pathological subtype was liposarcoma. All patients received concomitant resection of a median of 3 additional organs (range: 1-5), including 11 patients (40.7%) who underwent inferior vena cava resection and 1 patient underwent segmental superior mesenteric-portal vein resection. Microscopic tumor infiltration to the duodenum or pancreas was observed in 81.5% of patients. Major complications occurred in 40.7% of patients, the re-operation rate was 22.2%. One patient (3.7%) died from liver abscess postoperatively. During a median follow-up of 18.9 months, 15 patients (55.6%) developed locally recurrent disease, 2 patients (7.4%) also had pulmonary metastases additionally. Twelve patients (44.4%) died from local relapse eventually. Conclusions: PD during RPS resection is feasible and may be necessary to achieve complete resection. However, considering the complexity and risk, it should be performed by an experienced surgical team. The long-term survival benefit of this procedure should be verified by further large-scale multi-institutional studies.